A new thermodynamic description of the binary Bi-Te system using the associate solution and the Wagner-Schottky models. (December 2018) - Gierlotka, Wojciech
Abstract: The bismuth-tellurium system is a very important material that found application in thermoelectric devices. Interesting, the phase diagram of this system had many versions that did not agree one with another. Recently published research allowed for a precise description of phase relationship in this system; however, the proposed thermodynamic description was a simplification that not reflects physical properties of liquid phase and homogeneity range of thermoelectric phase Bi2 Te3 . In this work, the associate liquid solution and the Wagner-Schottky models were involved in the optimization, hence the existence of liquid clusters and homogeneity range of Bi2 Te3 were reproduced. Highlights: Associated solution model was used to describe a liquid phase. Wagner-Shottky model was used for modeling of homogeneity range of Bi2 Te3 . Good agreement between different kind of thermochemical and phase equilibria data and calculation was found. Partial pressure of Te2 over the Bi-Te system was calculated and compared with available experimental information. A good agreement between modeling and experiment was found.